Effect of row spacing and sowing direction on performance of wheat in Kandahar region of Afghanistan - Faiz, Mukhtar Ahmad; Dhar, Shiva; Baray, Shah Mahmood; Dass, Anchal; Khalili, Azizullah (Annals of Agricultural Research, 2016)
A field experiment was carried out at Tarnak Farm of Afghanistan National Agricultural Scienceand Technology University (ANASTU) Kandahar, Afghanistan during winter season of 2014-2015to study the effect of row spacing and sowing direction on growth and yield of wheat varieties. Theexperiment was laid out in FRBD and replicated thrice consisted of two varieties (Shisham Baghand PBW 154), three row spacing (15, 20 and 25 cm) and two sowing directions (East-West andNorth-South). Result revealed that more effective tillers m–2 (402.3) and grains spike–1 were obtainedfrom PBW 154 planted at 20 cm row spacing in East-West direction. Significantly higher 1000-grainweight (45.4 g) produced by PBW 154 sown at 20 cm row spacing in N-S direction. Higher grainyield (6.4 t ha–1) and harvest index (47.5%) were recorded from PBW 154 sown at 20 cm row spacingin E-W direction but straw and biological yields were higher in Shisham Bagh sown at 20 cm rowspacing in North-South direction.